Transparent display screen based on plasmon particles and its manufacturing process

By plating and annealing the metal particle layer on the transparent substrate of the transparent display screen, forming a core-shell structure, and plating a silica dielectric layer on it, the problem of insufficient observation angle, transparency and signal brightness in the prior art is solved, and a simple, fast and mass-produced color transparent display screen is realized, which improves display performance and reduces costs.

CN113031118BActive Publication Date: 2025-03-18SHENZHEN CHAOYI OPTOELECTRONICS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202110410929.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-04-16
Publication Date
2025-03-18
Estimated Expiration
2041-04-16

AI Technical Summary

Technical Problem

In the existing transparent display technology, the observation angle, transparency and signal brightness of the projected HUD still need to be improved, and the nanoparticle preparation process is complex and time-consuming, making it difficult to realize a simple, fast and mass-produced color transparent display screen.

Method used

The transparent display screen process based on plasmon particles is adopted, and the metal particle layers are sequentially plated on the transparent substrate, and the argon ion sputtering coating meter and electron beam thermal evaporation coating meter are used for coating. The silver-alumina, silver-titanium dioxide and gold-titanium dioxide core-shell structures are formed by combining annealing treatment and atomic layer deposition methods. Finally, the silica dielectric layer is plated on the metal particles to adjust the resonance wavelength.

Benefits of technology

It realizes a color transparent display with simple process, short cycle and mass production, improves display performance, reduces preparation costs, and has uniform distribution of metal particles and controllable resonance wavelength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113031118B_ABST
    Figure CN113031118B_ABST
Patent Text Reader

Abstract

The present invention discloses a transparent display screen based on plasmon particles, comprising a horizontally arranged transparent substrate, wherein a blue light display metal particle layer, a green light display metal particle layer and a red light display metal particle layer are sequentially arranged on the upper surface of the transparent substrate. The transparent display screen of the present invention comprises a transparent substrate and a metal nanoparticle layer for realizing red, green and blue light intensity scattering, wherein the metal nanoparticles have wavelength selective strong resonance scattering characteristics, so that a clear pattern can be displayed on the screen when light near the resonance wavelength is projected on the screen. Compared with the previous preparation method based on coating and drying of a silver nanoparticle solution, the production process of the present invention has the advantages of low cost, short preparation cycle, convenient tuning of the display wavelength and the like, and has important application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of transparent display, and in particular relates to a transparent display screen based on plasmon particles and a manufacturing process thereof. Background Art

[0002] In recent years, transparent display technology has attracted more and more attention. Due to its transparent display panel, it can be used as a head-up display (HUD), head mounted projection display (HMPD) and floating displays suitable for building windows and shop windows, etc., which has gradually become the development trend of contemporary display technology. Among them, HUD technology has developed rapidly. In the military field, it can project flight data onto the transparent display component directly in front of the driver, so that the driver can maintain a head-up state without affecting the acquisition of real-life information outside the cockpit, while looking at the navigation data and driving environment on the transparent display panel to guide driving. Therefore, it plays an extremely important role in improving driving quality, improving the combat effectiveness and reliability of aircraft, and ensuring the safety of drivers. As a result, civil airliners and some high-end cars have been installed and used one after another due to their convenience and safety, improving user driving experience, and the market prospects are broad. However, the viewing angle, transparency and signal light brightness of the projected HUD still need to be further improved.

[0003] With the rapid development of nano-processing and characterization technology, surface plasmon resonance of metal micro-nano structures has gradually become a research hotspot in current physics, chemistry, materials, information science, life science and other disciplines and their cross-fields. Studies have found that when nanoparticles with wavelength-selective surface plasmon resonance are applied to transparent displays, the particles selectively enhance the scattering of projected light and support a narrower mode linewidth in the visible light band, which has great potential in improving the performance of transparent displays.

[0004] Hsu et al. of the Massachusetts Institute of Technology in the United States used a silver ball structure that supports SP resonance and used the method of coating and spin coating this nanostructure to experimentally achieve a high-contrast transparent blue light display (CN105027184A). Saito et al. of the University of Tokyo in Japan used two scattering peaks obtained by the interaction between the SP resonance of silver nanocubic particles and the TiO2 substrate to experimentally achieve a transparent color transparent display. Ye et al. of Nanyang Technological University in Singapore used the SP resonance of the Ag@TiO2 core-shell structure to achieve a transparent green light display. However, the preparation process of the metal particles and the core-shell structure used is cumbersome and time-consuming, and it is necessary to ensure that the particles are evenly distributed in the matrix, which has high requirements on the preparation environment and preparation method. Recently, a related patent (CN108997687A) proposed a mixture of several nanoparticles that respond to red, green and blue light (limited bands are 660nm, 560nm and 450nm) to achieve color transparent display. The same problem is that the nanoparticles used in the preparation process require measuring instruments to assist in measurement, and the particle size accuracy requirements are high. Therefore, the preparation method is relatively complicated, and the film is also prepared by coating with a mixed solution, which has a long preparation cycle.

[0005] Therefore, it is necessary to develop a simple, time-saving, and mass-producible color transparent display preparation technology. Summary of the invention

[0006] In order to solve the deficiencies in the prior art, a transparent display screen based on plasmon particles and a manufacturing process thereof are provided, which have simple process, short manufacturing cycle and can be mass-produced.

[0007] To solve the above technical problems, the present invention adopts the following technical solution: a transparent display screen based on plasmon particles comprises a horizontally arranged transparent substrate, and a blue light display metal particle layer, a green light display metal particle layer and a red light display metal particle layer are sequentially arranged on the upper surface of the transparent substrate.

[0008] The blue light display metal particle layer includes a plurality of silver nanoparticles, the silver nanoparticles are wrapped with an aluminum oxide film, and a first silicon dioxide transparent medium layer is plated on the outside of the aluminum oxide film;

[0009] The radius of the silver nanoparticle is 30nm, the thickness of the aluminum oxide film is 10nm, the refractive index of the aluminum oxide film is 1.59, the refractive index of the first silicon dioxide transparent medium layer is 1.45, and the thickness of the first silicon dioxide medium layer is 120-200nm.

[0010] The green light display metal particle layer includes a plurality of silver nanoparticles, the outside of the silver nanoparticles is wrapped with a titanium dioxide film, and a second silicon dioxide transparent medium layer is plated on the outside of the titanium dioxide film;

[0011] The radius of the silver nanoparticle is 30nm, the thickness of the titanium dioxide film is 10nm, the refractive index of the titanium dioxide film is 2.45, the refractive index of the second silicon dioxide transparent medium layer is 1.45, and the thickness of the second silicon dioxide medium layer is 120-200nm.

[0012] The red light shows that the metal particle layer includes a number of gold nanoparticles, the outside of the gold nanoparticles is wrapped with a titanium dioxide film, and a third silicon dioxide transparent medium layer is coated on the outside of the titanium dioxide film;

[0013] The radius of the silver nanoparticle is 35nm, the thickness of the titanium dioxide film is 15nm, the refractive index of the titanium dioxide film is 2.45, the refractive index of the third silicon dioxide transparent medium layer is 1.45; the thickness of the third silicon dioxide medium layer is 120-200nm.

[0014] The manufacturing process of a transparent display screen based on plasmon particles includes the following steps:

[0015] (1) using an argon ion sputtering coating apparatus or an electron beam thermal evaporation coating apparatus to coat a layer of silver film on the surface of a transparent substrate, the material of the transparent substrate being glass, plastic, resin or polymer;

[0016] (2) placing the silver-plated transparent substrate into an annealing device for annealing;

[0017] (3) After annealing, silver nanoparticles are obtained on the surface of the transparent substrate. The size of the silver nanoparticles is related to the film thickness. The particle size is calculated based on the Mie scattering theory.

[0018] (4) Using atomic layer deposition method to wrap a layer of aluminum oxide film on the outside of silver nanoparticles to form a silver-aluminum oxide core-shell structure;

[0019] (5) using an argon ion sputtering coater or an electron beam thermal evaporation coater to coat a first layer of silicon dioxide transparent dielectric layer on the outside of the aluminum oxide film;

[0020] (6) coating a layer of silver film on the surface of the first silicon dioxide transparent medium layer in the manner as in step (1);

[0021] (7) placing the silver-plated transparent substrate into an annealing device for annealing in the manner of step (2);

[0022] (8) After annealing, silver nanoparticles are obtained. The size of the silver nanoparticles is related to the film thickness. The particle size is calculated based on Mie scattering theory.

[0023] (9) using the atomic layer deposition method as in step (4) to wrap a layer of titanium dioxide film around the outside of the silver nanoparticles to form a silver-titanium dioxide core-shell structure;

[0024] (10) coating a second transparent silicon dioxide dielectric layer on the outside of the titanium dioxide film in the manner of step (5);

[0025] (11) coating a layer of gold film on the surface of the second silicon dioxide transparent dielectric layer in the manner of step (1) or step (6);

[0026] (12) placing the transparent substrate coated with the gold film in an annealing device for annealing in the manner of step (2);

[0027] (13) After annealing, gold nanoparticles are obtained. The size of the gold nanoparticles is related to the film thickness. The particle size is calculated based on Mie scattering theory.

[0028] (14) using the atomic layer deposition method as in step (4) to wrap a layer of titanium dioxide film around the gold nanoparticles to form a gold-titanium dioxide core-shell structure;

[0029] (15) A third silicon dioxide dielectric layer is deposited on the outside of the titanium dioxide film in the same manner as in step (5).

[0030] Step (1) uses an electron beam thermal evaporation coating apparatus to coat a silver film on the glass surface. The specific steps are as follows: a clean 8 cm×8 cm optical glass is placed on a substrate holder of the electron beam thermal evaporation coating apparatus, silver particles with a purity of 99.99% are placed in a tungsten crucible for evaporation, the vacuum degree is drawn to below 5×10-4Pa, and coating is started; during the coating process, the coating rate can be controlled by controlling the electron beam current, and the film thickness can be controlled by adjusting the coating rate and time.

[0031] Step (1) silver is plated on the glass surface using an argon ion sputtering coating apparatus, and the specific steps are as follows: a cleaned 8 cm×8 cm optical glass is placed in a sample rod stage of the argon ion sputtering coating apparatus, the sample rod stage is pushed into the argon ion sputtering coating apparatus, and vacuum is drawn. When the vacuum degree is drawn to below 5×10-4Pa, sputtering coating is started; the working voltage and current of the electron gun are adjusted, and the recommended parameters are 7kv / 300uA, and the silver coating rate is 8nm / min; the size of the silver particles finally obtained is related to the coating time, and the time is controlled to 15S, 30S, 45S, 60S, and 75S respectively to obtain a film structure, wherein the silver particles of 30S-75S are island-shaped.

[0032] The annealing device in step (2) comprises a base, a cylindrical box is arranged on the base, the center line of the cylindrical box is arranged horizontally in the left-right direction, a plurality of heating tubes are evenly arranged on the inner circle of the cylindrical box along the circumferential direction, a hollow shaft is rotatably arranged between the center of the left panel and the center of the right panel of the cylindrical box, a hollow suction cup is fixedly arranged on opposite sides of the outer side of the hollow shaft, the left end of the hollow shaft passes through the left panel of the cylindrical box and is connected to a vacuum tube through a rotating joint, the vacuum tube is connected to a vacuum pump, a motor is arranged on the right side of the right panel of the cylindrical box, the main shaft of the motor is coaxially connected to the right end of the hollow shaft, a box door is arranged on the left panel of the cylindrical box, and an air inlet pipe is arranged on the upper part of the right panel of the cylindrical box;

[0033] Each heating tube is parallel to the center line of the cylindrical box, and the right end of each heating tube extends out of the right side panel of the cylindrical box and is fixedly connected to a terminal, all the terminals are connected in series through wires, and the wires are connected to the power cord; a temperature sensor is arranged in the cylindrical box; a cylindrical isolation net is fixedly arranged on the inner side of all heating tubes in the cylindrical box; a heat-insulating material layer is arranged on the outside of the cylindrical box and the outside of the box door; the hollow suction cup is a rectangular plate structure, and a rectangular cavity is provided in the center of the hollow suction cup; a side surface of the hollow suction cup fixedly connected to the hollow shaft is provided with a plurality of first suction ports at intervals along the length direction of the hollow shaft, and a plurality of second suction ports are evenly arranged on the other side surface of the hollow suction cup; two box doors are arranged on the left side panel of the cylindrical box, and the two box doors are symmetrical about the center line of the cylindrical box.

[0034] The specific process of the annealing treatment in step (2) is as follows: open the two box doors, first rotate the two hollow suction cups to a vertical state, then put the two pieces of glass coated with silver film into the cylindrical box, the uncoated side of the glass contacts the surface of the hollow suction cup, turn on the vacuum pump, the vacuum pump firmly adsorbs the two pieces of glass on the hollow suction cup through the vacuum tube, the hollow shaft, the first suction port and the second suction port, then close the two box doors, start the power of the motor and the heating tube, the heating tube heats the internal space of the closed cylindrical box, the motor drives the hollow shaft to rotate, the hollow shaft drives the two hollow suction cups to rotate, and the two coated glasses adsorbed on the hollow suction cups also rotate. At the same time, 0.01MPa of protective nitrogen and reducing hydrogen are filled into the cylindrical box through the air inlet pipe. Since there is an air permeable gap between the glass and the hollow suction cup, the air inside the cylindrical box is replaced by protective nitrogen and reducing hydrogen while the hollow suction cup is adsorbed. Then the heating tube is heated to 300℃ at a heating rate of 5℃ / min. The temperature monitoring is transmitted to the PLC controller through the temperature sensor. The PLC controller adjusts the power supply to the power supply current of the heating tube. After keeping warm at 300℃ for 30 minutes, the power of the motor and the heating tube is turned off first, then the box door is opened, the vacuum pump is turned off, and the two pieces of glass are taken out to complete the annealing process.

[0035] The specific process of step (4) is: using trimethylaluminum and high-purity water as reaction sources, high-purity N2 as purge gas, growing alumina transparent medium outside the metal nanoparticles, deposition temperature: 120°C, trimethylaluminum pulse time: 0.2-0.6S; high-purity water pulse time: 0.3S; purge time: 10S; cycle period: 25 times.

[0036] With the above technical solution, the thickness of the metal film depends on the coating growth rate and time. The metal can be silver, gold or aluminum, etc. If the structure of the metal particles is required to be a core-shell structure, after the metal particles are formed, the atomic layer deposition (ALD) method is used to grow a transparent dielectric layer on the outside of the metal particles. Finally, a transparent film is coated on the metal particles. This process can prevent the metal particles from oxidizing in the air and can also adjust the resonance position. The film material is transparent and not unique. The uniform distribution of metal particles is achieved by coating.

[0037] The annealing device uses a vacuum pump to evacuate the hollow suction cup to adsorb the coated glass, and a motor drives the hollow suction cup and two pieces of coated glass to rotate slowly. This not only increases the temperature of the heated surface to remain consistent, but also allows the coating to dynamically contact with protective nitrogen and reducing hydrogen, thereby improving the processing quality of the annealing process.

[0038] Several heating tubes are evenly arranged along the circumference of the cylindrical box, which can also improve the uniformity of heating the coating.

[0039] The isolation net not only has good heat permeability, but also prevents the glass from touching the heating tube when taking and placing the glass.

[0040] The heat insulation material layer (polyurethane heat insulation material may be used) can prevent heat loss and improve heating efficiency.

[0041] The annealing device uses a cylindrical box with the characteristics of small size and compact structure. The entire annealing process is also easy to operate. The vacuum adsorption method is not only firmly fixed, but also can be rotated during the treatment process, which improves the consistency of the coating surface temperature and greatly improves the product quality.

[0042] In summary, the present invention as a whole has the following beneficial effects:

[0043] (1) The present invention provides a new process for manufacturing a color transparent display screen based on plasmon particles. An argon ion sputtering coating apparatus and an electron beam thermal evaporation coating apparatus are used to coat a metal film on an optical glass substrate, and then metal particles with a strong wavelength selective optical antenna function are obtained after annealing. The ALD method is used to wrap a layer of transparent medium on the metal particles to adjust different resonance wavelengths, thereby achieving red, green and blue transparent displays. A layer of silicon dioxide environmental medium is then coated on the top, which can not only adjust the resonance position of the metal particles, but also effectively prevent the metal particles from oxidizing. Transparent display films of red, green and blue colors are prepared in turn, and finally the desired transparent display screen is obtained. The preparation process is simple, the metal particles are evenly distributed, and the size of the metal particles can be controlled by controlling the coating time.

[0044] (2) The price of the metal target used for coating is much lower than the metal particles obtained by other methods. It is low-cost and has broad market prospects.

[0045] (3) The preparation process of the present invention is short, time-saving and more efficient.

[0046] (4) The present invention can form nanoparticles with regular shape, controllable size and resonance band through simple coating and annealing processes, thereby effectively absorbing blue light and reducing the yellowing of the film, which has important application value.

[0047] (5) The transparent display screen includes a transparent substrate and a metal nanoparticle layer that can achieve strong scattering of red, green and blue light. These metal nanoparticles have wavelength-selective strong resonant scattering characteristics. Therefore, when light near the resonant wavelength is projected on the screen, a clear pattern can be displayed on the screen. Moreover, since the screen is almost transparent to light of non-resonant wavelengths, it does not affect the observation of objects behind it, thereby achieving transparent display. The method adopts the method of physical vapor deposition throughout the process. First, a metal film is plated on the transparent substrate; then it is placed in an annealing device for annealing treatment to form metal nanoparticles on the transparent substrate; finally, a dielectric layer with wavelength adjustment function and a silicon dioxide environment medium are grown on the metal particles to adjust the position of the resonant scattering, thereby adjusting the displayed color. By using the mode of coating first and then annealing, changing the coating time can easily obtain metal nanoparticles of different sizes, thereby achieving the adjustment of the resonant wavelength. Compared with the previous preparation method based on coating and drying of silver nanoparticle solution, this process has the advantages of low cost, short preparation cycle, and convenient tuning of display wavelength, and has important application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 It is a schematic structural diagram of the annealing device in the present invention;

[0049] Figure 2 yes Figure 1 Right view of;

[0050] Figure 3 yes Figure 1 Left view of

[0051] Figure 4 It is the extinction, scattering and absorption spectra of plasmonic particles that realize blue light display (420-500nm) in quartz environment;

[0052] Figure 5 It is the extinction, scattering and absorption spectra of plasmon particles that realize green light display (500-560nm) in quartz environment;

[0053] Figure 6 It is the extinction, scattering and absorption spectra of plasmonic particles that realize red light display (620-760nm) in quartz environment;

[0054] Figure 7 The SEM morphology of the silver film deposited on the optical glass substrate by the argon ion sputtering coater at different times before and after annealing;

[0055] Figure 8 It is a schematic diagram of the layered structure of the transparent display screen of the present invention. DETAILED DESCRIPTION

[0056] like Figure 8 As shown, the transparent display screen based on plasmon particles of the present invention comprises a horizontally arranged transparent substrate 23, and a blue light display metal particle layer 24, a green light display metal particle layer 25 and a red light display metal particle layer 26 are sequentially arranged on the upper surface of the transparent substrate 23. The upper and lower positions of the blue light display metal particle layer 24, the green light display metal particle layer 25 and the red light display metal particle layer 26 can be adjusted arbitrarily.

[0057] The blue light display metal particle layer 24 includes a plurality of silver nanoparticles, the silver nanoparticles are wrapped with an aluminum oxide film, and a first silicon dioxide transparent medium layer is plated on the aluminum oxide film.

[0058] The radius of the silver nanoparticle is 30nm, the thickness of the aluminum oxide film is 10nm, the refractive index of the aluminum oxide film is 1.59, the refractive index of the first silicon dioxide transparent medium layer is 1.45, and the thickness of the first silicon dioxide medium layer is 120-200nm.

[0059] The green light display metal particle layer 25 includes a plurality of silver nanoparticles, the outside of the silver nanoparticles is wrapped with a titanium dioxide film, and a second silicon dioxide transparent medium layer is plated on the outside of the titanium dioxide film;

[0060] The radius of the silver nanoparticle is 30nm, the thickness of the titanium dioxide film is 10nm, the refractive index of the titanium dioxide film is 2.45, the refractive index of the second silicon dioxide transparent medium layer is 1.45, and the thickness of the second silicon dioxide medium layer is 120-200nm.

[0061] The red light display metal particle layer 26 includes a plurality of gold nanoparticles, the gold nanoparticles are coated with a titanium dioxide film, and a third silicon dioxide transparent medium layer is plated on the titanium dioxide film;

[0062] The radius of the silver nanoparticle is 35nm, the thickness of the titanium dioxide film is 15nm, the refractive index of the titanium dioxide film is 2.45, the refractive index of the third silicon dioxide transparent medium layer is 1.45; the thickness of the third silicon dioxide medium layer is 120-200nm.

[0063] The manufacturing process of a transparent display screen based on plasmon particles includes the following steps:

[0064] (1) using an argon ion sputtering coating apparatus or an electron beam thermal evaporation coating apparatus to coat a layer of silver film on the upper surface of the transparent substrate 23, wherein the material of the transparent substrate 23 is glass, plastic, resin or polymer;

[0065] (2) placing the silver-plated transparent substrate 23 into an annealing device for annealing;

[0066] (3) After annealing, silver nanoparticles are obtained on the surface of the transparent substrate 23. The size of the silver nanoparticles is related to the film thickness. The particle size is calculated based on the Mie scattering theory.

[0067] (4) Using atomic layer deposition method to wrap a layer of aluminum oxide film on the outside of silver nanoparticles to form a silver-aluminum oxide core-shell structure;

[0068] (5) using an argon ion sputtering coater or an electron beam thermal evaporation coater to coat a first layer of silicon dioxide transparent dielectric layer on the outside of the aluminum oxide film;

[0069] (6) coating a layer of silver film on the surface of the first silicon dioxide transparent medium layer in the manner as in step (1);

[0070] (7) placing the silver-plated transparent substrate 23 into an annealing device for annealing in the manner of step (2);

[0071] (8) After annealing, silver nanoparticles are obtained. The size of the silver nanoparticles is related to the film thickness. The particle size is calculated based on Mie scattering theory.

[0072] (9) using the atomic layer deposition method as in step (4) to wrap a layer of titanium dioxide film around the outside of the silver nanoparticles to form a silver-titanium dioxide core-shell structure;

[0073] (10) coating a second transparent silicon dioxide dielectric layer on the outside of the titanium dioxide film in the manner of step (5);

[0074] (11) coating a layer of gold film on the surface of the second silicon dioxide transparent dielectric layer in the manner of step (1) or step (6);

[0075] (12) placing the gold-plated transparent substrate 23 into an annealing device for annealing in the manner of step (2);

[0076] (13) After annealing, gold nanoparticles are obtained. The size of the gold nanoparticles is related to the film thickness. The particle size is calculated based on Mie scattering theory.

[0077] (14) using the atomic layer deposition method as in step (4) to wrap a layer of titanium dioxide film around the gold nanoparticles to form a gold-titanium dioxide core-shell structure;

[0078] (15) A third silicon dioxide dielectric layer is deposited on the outside of the titanium dioxide film in the same manner as in step (5).

[0079] Step (1) uses an electron beam thermal evaporation coating apparatus to coat a silver film on the glass surface. The specific steps are as follows: a clean 8 cm×8 cm optical glass is placed on a substrate holder of the electron beam thermal evaporation coating apparatus, silver particles with a purity of 99.99% are placed in a tungsten crucible for evaporation, the vacuum degree is drawn to below 5×10-4Pa, and coating is started; during the coating process, the coating rate can be controlled by controlling the electron beam current, and the film thickness can be controlled by adjusting the coating rate and time.

[0080] Step (1) silver is plated on the glass surface using an argon ion sputtering coating apparatus, and the specific steps are as follows: a cleaned 8 cm×8 cm optical glass is placed in a sample rod stage of the argon ion sputtering coating apparatus, the sample rod stage is pushed into the argon ion sputtering coating apparatus, and vacuum is drawn. When the vacuum degree is drawn to below 5×10-4Pa, sputtering coating is started; the working voltage and current of the electron gun are adjusted, and the recommended parameters are 7kv / 300uA, and the silver coating rate is 8nm / min; the size of the silver particles finally obtained is related to the coating time, and the time is controlled to 15S, 30S, 45S, 60S, and 75S respectively to obtain a film structure, wherein the silver particles of 30S-75S are island-shaped.

[0081] like Figure 1-Figure 3As shown, the annealing device in step (2) comprises a base 1, on which a cylindrical box 2 is provided, the center line of the cylindrical box 2 is horizontally arranged in the left-right direction, the inner circle of the cylindrical box 2 is evenly provided with a plurality of heating tubes 3 in the circumferential direction, the cylindrical box 2, a hollow shaft 4 is rotatably provided between the center of the left panel and the center of the right panel of the cylindrical box 2, the right end of the hollow shaft 4 is blocked, and a hollow suction cup 5 is fixedly provided on the opposite sides of the outside of the hollow shaft 4, the left end of the hollow shaft 4 passes through the left panel of the cylindrical box 2 and is connected to a vacuum pipe 7 through a rotary joint 6, the vacuum pipe 7 is connected to a vacuum pump 8, a motor 9 is provided on the right side of the right panel of the cylindrical box 2 (connected by a connecting plate 10 and a bolt 11), the main shaft of the motor 9 is coaxially connected to the right end of the hollow shaft 4, a box door 12 is provided on the left panel of the cylindrical box 2, and an air intake pipe 13 is provided on the upper part of the right panel of the cylindrical box 2.

[0082] Each heating tube 3 is parallel to the center line of the cylindrical box 2. The right end of each heating tube 3 extends out of the right panel of the cylindrical box 2 and is fixedly connected to a terminal 14. All the terminals 14 are connected in series through a wire 15, and the wire 15 is connected to a power line 16. A temperature sensor 17 is provided in the cylindrical box 2. A cylindrical isolation net 18 is fixedly provided on the inner side of all heating tubes 3 in the cylindrical box 2. A heat insulation material layer 19 is provided on the outside of the cylindrical box 2 and the outside of the box door 12. The hollow suction cup 5 is a rectangular plate structure, and the center of the hollow suction cup 5 has a rectangular cavity 20. A side surface of the hollow suction cup 5 fixedly connected to the hollow shaft 4 is provided with a plurality of first suction ports 21 spaced apart along the length direction of the hollow shaft 4, and a plurality of second suction ports 22 are evenly provided on the other side surface of the hollow suction cup 5. Two box doors 12 are provided on the left panel of the cylindrical box 2, and the two box doors 12 are symmetrical about the center line of the cylindrical box 2.

[0083] The specific process of the annealing treatment in step (2) is as follows: open the two box doors 12, first rotate the two hollow suction cups 5 to a vertical state, then put the two pieces of glass coated with silver film into the cylindrical box 2, the side of the glass without silver film is in contact with the surface of the hollow suction cup 5, turn on the vacuum pump 8, the vacuum pump 8 firmly adsorbs the two pieces of glass on the hollow suction cup 5 through the vacuum tube 7, the hollow shaft 4, the first suction port 21 and the second suction port 22, then close the two box doors 12, start the power of the motor 9 and the heating tube 3, the heating tube 3 heats the internal space of the closed cylindrical box 2, the motor 9 drives the hollow shaft 4 to rotate, and the hollow shaft 4 drives the two hollow suction cups 5 to rotate (the rotary joint 6 is set, and the vacuum tube 7 does not move), and the two coated glass adsorbed on the hollow suction cup 5 The glass also rotates, and at the same time, 0.01MPa of protective nitrogen and reducing hydrogen are filled into the cylindrical box 2 through the air inlet pipe 13. Since there is an air permeable gap between the glass and the hollow suction cup 5, the air inside the cylindrical box 2 is replaced by protective nitrogen and reducing hydrogen while the hollow suction cup 5 is adsorbed. Then the heating speed of the heating tube 3 is increased to 300°C at 5°C / min. The temperature monitoring is transmitted to the PLC controller through the temperature sensor 17. The PLC controller adjusts the power supply to the power supply current of the heating tube 3. After keeping warm at 300°C for 30 minutes, the power of the motor 9 and the heating tube 3 is turned off first, and then the box door 12 is opened, the vacuum pump 8 is turned off, and the two pieces of glass are taken out to complete the annealing process.

[0084] The specific process of step (4) is: using trimethylaluminum and high-purity water as reaction sources, high-purity N2 as purge gas, growing alumina transparent medium outside the metal nanoparticles, deposition temperature: 120°C, trimethylaluminum pulse time: 0.2-0.6S; high-purity water pulse time: 0.3S; purge time: 10S; cycle period: 25 times.

[0085] A vacuum pump 8 is used to evacuate the hollow suction cup 5 to adsorb the coated glass, and a motor 9 is used to drive the hollow suction cup 5 and the two coated glasses to rotate slowly. This not only improves the temperature of the heated surface to remain consistent, but also allows the coating to dynamically contact with the protective nitrogen and reducing hydrogen, thereby improving the processing quality of the annealing process.

[0086] A plurality of heating tubes 3 are evenly arranged along the circumferential direction of the cylindrical box 2, which can also improve the uniformity of heating the coating.

[0087] The isolation net 18 not only has good heat permeability, but also prevents the glass from touching the heating tube 3 when taking or placing the glass.

[0088] The heat insulating material layer 19 (polyurethane heat insulating material may be used) can prevent heat loss and improve heating efficiency.

[0089] The annealing device adopts a cylindrical box 2 with the characteristics of small size and compact structure. The entire annealing process is also easy to operate. The vacuum adsorption method is not only firmly fixed, but also can be rotated during the treatment process, which improves the consistency of the coating surface temperature and greatly improves the product quality.

[0090] Figure 4 It is the extinction, scattering and absorption spectra of plasmonic particles that realize blue light display (420-500nm) under quartz (transparent substrate 23) environment. The particles used are silver-aluminum oxide core-shell structure, in which the radius of the inner silver particles can be any size between 15-35nm, and the thickness of the shell medium aluminum oxide can be any size between 0-10nm. In addition, the particles can also be pure silver particles with a radius between 15-35nm; aluminum-titanium dioxide core-shell structure, the aluminum core radius is 25-35nm, and the titanium dioxide thickness is 10-15nm.

[0091] Figure 5 It is the extinction, scattering and absorption spectra of plasmonic particles that realize green light display (500-560nm) in quartz environment. The particles used are silver-titanium dioxide core-shell structure, in which the radius of the inner silver particle can be any size from 20-35nm, and the thickness of the shell medium aluminum oxide can be any size from 10-20nm. In addition, silver-aluminum oxide or silver-silicon dioxide core-shell structure can also be used in titanium dioxide environment. For the silver-aluminum oxide core-shell structure, the radius of the silver core is 25-30nm, and the thickness of the aluminum oxide is 10-15nm; for the silver-silicon dioxide core-shell structure, the radius of the silver core is 25-30nm, and the thickness of the silicon dioxide is 10-15nm.

[0092] Figure 6 To achieve the extinction, scattering and absorption spectra of plasmon particles for red light display (620-760nm) in a quartz environment, the particles used are gold-titanium dioxide core-shell structures, where the radius of the inner silver particles can be any size from 30-50nm, and the thickness of the shell dielectric aluminum oxide can be any size from 5-30nm. In addition, pure gold particles can be used in a titanium dioxide environment with a radius between 20-35nm.

[0093] Figure 7 The SEM morphology of the silver film coated on the optical glass substrate by the argon ion sputtering coater at different times before and after annealing. ac is the SEM morphology of the coating at 15S, 45S, and 75S, with film thickness of 2nm, 6nm, and 10nm respectively, and df is the corresponding SEM morphology after annealing, forming spherical particles with a certain shape, and the average particle size is 10-15nm, 30-35nm, and 50-55nm.

[0094] The above embodiments illustrate the basic principles and features of the present invention, but the above only illustrates the preferred embodiments of the present invention and is not limited to the embodiments. Under the inspiration of this patent, a person skilled in the art can make many forms of deformation and improvement without departing from the scope of protection of the present invention and the claims, which are all within the protection scope of the present invention. Therefore, the patent and protection scope of the present invention shall be subject to the attached claims.

Claims

1. A process for manufacturing a transparent display screen based on plasmon particles, characterized in that: The transparent display screen based on plasmon particles comprises a horizontally arranged transparent substrate, and a blue light display metal particle layer, a green light display metal particle layer and a red light display metal particle layer are sequentially arranged on the upper surface of the transparent substrate; The blue light display metal particle layer includes a plurality of silver nanoparticles, the silver nanoparticles are wrapped with an aluminum oxide film, and a first silicon dioxide transparent medium layer is plated on the outside of the aluminum oxide film; The radius of the silver nanoparticles is 30 nm, the thickness of the aluminum oxide film is 10 nm, the refractive index of the aluminum oxide film is 1.59, the refractive index of the first silicon dioxide transparent medium layer is 1.45, and the thickness of the first silicon dioxide medium layer is 120-200 nm; The green light display metal particle layer includes a plurality of silver nanoparticles, the outside of the silver nanoparticles is wrapped with a titanium dioxide film, and a second silicon dioxide transparent medium layer is plated on the outside of the titanium dioxide film; The radius of the silver nanoparticles is 30 nm, the thickness of the titanium dioxide film is 10 nm, the refractive index of the titanium dioxide film is 2.45, the refractive index of the second silicon dioxide transparent medium layer is 1.45, and the thickness of the second silicon dioxide medium layer is 120-200 nm; The red light shows that the metal particle layer includes a number of gold nanoparticles, the outside of the gold nanoparticles is wrapped with a titanium dioxide film, and a third silicon dioxide transparent medium layer is coated on the outside of the titanium dioxide film; The radius of the silver nanoparticles is 35nm, the thickness of the titanium dioxide film is 15nm, the refractive index of the titanium dioxide film is 2.45, the refractive index of the third silicon dioxide transparent medium layer is 1.45; the thickness of the third silicon dioxide medium layer is 120-200nm; The manufacturing process of the transparent display screen based on plasmon particles comprises the following steps: (1) using an argon ion sputtering coating apparatus or an electron beam thermal evaporation coating apparatus to coat a layer of silver film on the surface of a transparent substrate, the material of the transparent substrate being glass, plastic, resin or polymer; (2) placing the silver-plated transparent substrate into an annealing device for annealing; (3) After annealing, silver nanoparticles are obtained on the surface of the transparent substrate. The size of the silver nanoparticles is related to the film thickness. The particle size is calculated based on the Mie scattering theory. (4) Using atomic layer deposition method to wrap a layer of aluminum oxide film on the outside of silver nanoparticles to form a silver-aluminum oxide core-shell structure; (5) using an argon ion sputtering coater or an electron beam thermal evaporation coater to coat a first layer of silicon dioxide transparent dielectric layer on the outside of the aluminum oxide film; (6) coating a layer of silver film on the surface of the first silicon dioxide transparent medium layer in the manner as in step (1); (7) placing the silver-plated transparent substrate into an annealing device for annealing in the manner of step (2); (8) After annealing, silver nanoparticles are obtained. The size of the silver nanoparticles is related to the film thickness. The particle size is calculated based on Mie scattering theory. (9) using the atomic layer deposition method as in step (4) to wrap a layer of titanium dioxide film around the outside of the silver nanoparticles to form a silver-titanium dioxide core-shell structure; (10) coating a second transparent silicon dioxide dielectric layer on the outside of the titanium dioxide film in the manner of step (5); (11) coating a layer of gold film on the surface of the second silicon dioxide transparent dielectric layer in the manner of step (1) or step (6); (12) placing the transparent substrate coated with the gold film in an annealing device for annealing in the manner of step (2); (13) After annealing, gold nanoparticles are obtained. The size of the gold nanoparticles is related to the film thickness. The particle size is calculated based on Mie scattering theory. (14) using the atomic layer deposition method as in step (4) to wrap a layer of titanium dioxide film around the gold nanoparticles to form a gold-titanium dioxide core-shell structure; (15) Plating a third silicon dioxide dielectric layer on the outside of the titanium dioxide film in the same manner as in step (5); The annealing device in step (2) comprises a base, a cylindrical box is arranged on the base, the center line of the cylindrical box is arranged horizontally in the left-right direction, a plurality of heating tubes are evenly arranged on the inner circle of the cylindrical box along the circumferential direction, a hollow shaft is rotatably arranged between the center of the left panel and the center of the right panel of the cylindrical box, a hollow suction cup is fixedly arranged on opposite sides of the outer side of the hollow shaft, the left end of the hollow shaft passes through the left panel of the cylindrical box and is connected to a vacuum tube through a rotating joint, the vacuum tube is connected to a vacuum pump, a motor is arranged on the right side of the right panel of the cylindrical box, the main shaft of the motor is coaxially connected to the right end of the hollow shaft, a box door is arranged on the left panel of the cylindrical box, and an air inlet pipe is arranged on the upper part of the right panel of the cylindrical box; Each heating tube is parallel to the center line of the cylindrical box, and the right end of each heating tube extends out of the right side panel of the cylindrical box and is fixedly connected to a terminal, all the terminals are connected in series through wires, and the wires are connected to the power cord; a temperature sensor is arranged in the cylindrical box; a cylindrical isolation net is fixedly arranged on the inner side of all heating tubes in the cylindrical box; a heat-insulating material layer is arranged on the outside of the cylindrical box and the outside of the box door; the hollow suction cup is a rectangular plate structure, and a rectangular cavity is provided in the center of the hollow suction cup; a side surface of the hollow suction cup fixedly connected to the hollow shaft is provided with a plurality of first suction ports at intervals along the length direction of the hollow shaft, and a plurality of second suction ports are evenly arranged on the other side surface of the hollow suction cup; two box doors are arranged on the left side panel of the cylindrical box, and the two box doors are symmetrical about the center line of the cylindrical box.

2. The process for manufacturing a transparent display screen based on plasmon particles according to claim 1, characterized in that: Step (1) uses an electron beam thermal evaporation coating apparatus to coat a silver film on the glass surface. The specific steps are as follows: a clean 8 cm×8 cm optical glass is placed on a substrate holder of the electron beam thermal evaporation coating apparatus, silver particles with a purity of 99.99% are placed in a tungsten crucible for evaporation, the vacuum degree is drawn to below 5×10-4Pa, and coating is started; during the coating process, the coating rate can be controlled by controlling the electron beam current, and the film thickness can be controlled by adjusting the coating rate and time.

3. The process for manufacturing a transparent display screen based on plasmon particles according to claim 1, characterized in that: Step (1) silver is plated on the glass surface using an argon ion sputtering coating apparatus, and the specific steps are as follows: a cleaned 8 cm×8 cm optical glass is placed in a sample rod stage of the argon ion sputtering coating apparatus, the sample rod stage is pushed into the argon ion sputtering coating apparatus, and vacuum is drawn. When the vacuum degree is drawn to below 5×10-4Pa, sputtering coating is started; the working voltage and current of the electron gun are adjusted, and the recommended parameters are 7kv / 300uA, and the silver coating rate is 8nm / min; the size of the silver particles finally obtained is related to the coating time, and the time is controlled to 15S, 30S, 45S, 60S, and 75S respectively to obtain a film structure, wherein the silver particles of 30S-75S are island-shaped.

4. The process for manufacturing a transparent display screen based on plasmon particles according to claim 1, characterized in that: The specific process of the annealing treatment in step (2) is as follows: open the two box doors, first rotate the two hollow suction cups to a vertical state, then put the two pieces of glass coated with silver film into the cylindrical box, the uncoated side of the glass contacts the surface of the hollow suction cup, turn on the vacuum pump, the vacuum pump firmly adsorbs the two pieces of glass on the hollow suction cup through the vacuum tube, the hollow shaft, the first suction port and the second suction port, then close the two box doors, start the power of the motor and the heating tube, the heating tube heats the internal space of the closed cylindrical box, the motor drives the hollow shaft to rotate, the hollow shaft drives the two hollow suction cups to rotate, and the two coated glasses adsorbed on the hollow suction cups also rotate. At the same time, 0.01MPa of protective nitrogen and reducing hydrogen are filled into the cylindrical box through the air inlet pipe. Since there is an air permeable gap between the glass and the hollow suction cup, the air inside the cylindrical box is replaced by protective nitrogen and reducing hydrogen while the hollow suction cup is adsorbed. Then the heating tube is heated to 300℃ at a heating rate of 5℃ / min. The temperature monitoring is transmitted to the PLC controller through the temperature sensor. The PLC controller adjusts the power supply to the power supply current of the heating tube. After keeping warm at 300℃ for 30 minutes, the power of the motor and the heating tube is turned off first, then the box door is opened, the vacuum pump is turned off, and the two pieces of glass are taken out to complete the annealing process.

5. The process for manufacturing a transparent display screen based on plasmon particles according to claim 1, characterized in that: The specific process of step (4) is: using trimethylaluminum and high-purity water as reaction sources, high-purity N2 as purge gas, growing alumina transparent medium outside the metal nanoparticles, deposition temperature: 120°C, trimethylaluminum pulse time: 0.2-0.6S; high-purity water pulse time: 0.3S; purge time: 10S; cycle period: 25 times.

Citation Information

Patent Citations

  • Self-healing transparent display film and preparation method and application thereof

    CN108997687A

  • Preparation method of Ag-SiO2-Ag nanosphere array

    CN104692827A

  • Methods and apparatus for transparent display using scattering nanoparticles

    CN105027184A

  • Transparent display screen based on plasmon particles

    CN214474058U

  • Laboratory transparent display screen coating and annealing device

    CN214504840U